Investigation of Power Quality Disturbances in an Electric Arc Furnace - Vinayaka, K. U.; Puttaswamy, P. S. (Asian Journal of Electrical Sciences, 2018)
Stochastic performance of an electric arc furnace (EAF) has drawn researcher’s attention due to power quality problems introduced by EAF operation. In this paper, Electric arc furnace is modeled to investigate power quality problems. Voltage flicker, harmonics and inter-harmonics are the main power quality disturbances that arise in the electrical network as a result of arc furnace operation due to the non-linear nature of EAF. A time domain model is derived to study the behavior in various operating conditions (melting and refining). The characteristic modeling of an EAF is carried out in MATLAB (Simulink).